ANALYSIS OF AMINA WADUD'S HERMENEUTIC WEAKNESSES THROUGH WASATIYYAH YUSUF QARDHAWI'S PERSPECTIVE - Azizah, Khansa' (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2023)
ABSTRACT The emergence of some activists from the feminist movement who consider the need for deconstruction and reconstruction as well as interpretation of the Al-Qur'an. This case is aimed at achieving a fairer meaning, and no party is marginalized. Amina Wadud is one of the feminist figures who is active and active in this field. Various issues of injustice contained in the Al-Qur'an are explained again according to his point of view. However, the spirit of interpretation with a hermeneutical style of gender equality needs to be analyzed from a wasatiyyah perspective; in this case, the author takes Yusuf Qardhawi's wasatiyyah principle. This writing was carried out using qualitative research methods based on data and library literature, data processing using concept analysis, and deductive-inductive analysis techniques in an exciting conclusion. Amina Wadud's description of thinking starts from the concept of human creation, so the main idea is called the hermeneutics of monotheism. Then, in applying the derivative language, it prioritizes ideal moral values ​​as ideas from Fazlur Rahman's ideas. However, in Yusuf Qardhawi's wasatiyyah principle, there is an impression of imposing one's will and only focusing on issues of injustice, making the hermeneutic concept of gender equality less suitable to be applied. There is still a need for further exploration and interpretation rules that need to be taken into account. Even in its application, some characteristics of Islamic teachings tend to be ignored. ABSTRAK Munculnya sebagian aktivis dari gerakan feminisme menganggap perlunya dekonstruksi dan rekonstruksi sekaligus terhadap tafsir Al-Qur'an. Hal ini ditujukan untuk mencapai makna yang lebih adil dan tidak ada pihak yang termarjinalkan. Amina Wadud adalah salah satu tokoh feminis yang aktif dan bergerak dalam bidang ini. Berbagai isu ketidakadilan yang terkandung dalam nas Al-Qur'an diuraikan kembali sesuai cara pandangnya. Namun, semangat penafsiran dengan corak hermeneutika kesetaraan gender perlu dianalisa dengan perspektif wasatiyyah, yang dalam hal ini penulis mengambil prinsip wasatiyyah Yusuf Qardhawi. Penulisan ini dilakukan dengan metode penelitian kualitatif berdasarkan data dan literatur kepustakaan, pengolahan data dengan analisis konsep dan teknik analisa secara deduktif-induktif. Dalam menarik kesimpulan. Uraian pemikiran Amina Wadud dimulai dari konsep penciptaan manusia menjadikan ide utamanya disebut hermeneutika tauhid. Kemudian dalam penerapan bahasan turunannya lebih mengedepankan nilai ideal moral sebagai ide dari gagasan Fazlur Rahman. Namun, dalam prinsip wasatiyyah Yusuf Qardhawi, didapati kesan akan memaksakan kehendak dan hanya fokus pada permasalahan ketidakdilan membuat konsep hermeneutika kesetaraan gender ini kurang sesuai untuk diaplikasikan begitu saja. Masih perlunya pendalaman dan kaidah penafsiran yang perlu diperhatikan. Bahkan dalam implementasinya, sebagian karakteristik ajaran Islam sendiri cenderung diabaikan.